New frog-type Dibenzo[a, c][1, 2, 5]thiadiazolo[3, 4-i]phenazine heterocyclic derivatives with aggregation-enhanced one- and two-photon excitation NIR fluorescence. (June 2018) - Lu, Yuansheng; Sun, Qikun; Zhang, Zhenzhen; Tang, Liangliang; Shen, Xin; Xue, Shanfeng; Yang, Wenjun
Abstract: Enabling organic fused heterocycles to exhibit aggregation-induced (or enhanced) near infrared (NIR) emission (AIE/AEE) and solution processability is very interesting but rarely reported since the large π-plane and the strong intramolecular charge transfer are prone to quench the fluorescence emission. In this article, a new solution-processable donor–acceptor frog-type dibenzo[ a, c ][1, 2, 5]thiadiazolo[3, 4- i ]- phenazine (DTP) derivative was designed and synthesized. It was characteristic of strong electron donors and solubilizing alkoxyphenyl groups linking respectively at the 3, 6- and 10, 14-positions of DTP core. The existence of multiple twisted and rotatable aryl moieties enabled this kind of fused heterocycles to exhibit aggregation-enhanced emission (AEE) feature. Benefiting from the extended π-plane and AEE effect, the very large 2PA cross section and the aqueous aggregation-enhanced one- and two-photon excitation NIR fluorescence were achieved, and the preliminary experiment evidenced its applicable in fluorescence bioimaging. Graphical abstract: A fused heterocycle is designed as AIE one- and two-photon NIR emitter through manipulating the linking positions of functional groups. Highlights: A new dibenzo[ a, c ][1, 2, 5]thiadiazolo[3, 4- i ]phenazine derivative (DBTP) was designed and synthesized. DBTP exhibits the aggregation-enhanced emission and NIR fluorescence in aggregation states. The large two-photon absorption cross section (5500 GM) was achieved. Aggregation-enhanced one- and two-photon excitation NIR fluorescence (more 20-fold) were achieved. The preliminary examination indicated that DBTP was applicable in bioimaging.